EPISTASIS, PLEIOTROPY, AND THE MUTATION LOAD IN SEXUAL AND ASEXUAL POPULATIONS. (1st January 2014) - Roze, Denis; Blanckaert, Alexandre
Abstract: Mutation may impose a substantial load on populations, which varies according to the reproductive mode of organisms. Over the past years, various authors used adaptive landscape models to predict the long‐term effect of mutation on mean fitness; however, many of these studies assumed very weak mutation rates, so that at most one mutation segregates in the population. In this article, we derive several simple approximations (confirmed by simulations) for the mutation load at high mutation rate ( U ), using a general model that allows us to play with the number of selected traits ( n ), the degree of pleiotropy of mutations, and the shape of the fitness function (which affects the average sign and magnitude of epistasis among mutations). When mutations have strong fitness effects, the equilibrium fitness W ¯ of sexuals and asexuals is close to e − U ; under weaker mutational effects, sexuals reach a different regime where W ¯ is a simple function of U and of a parameter describing the shape of the fitness function. Contrarily to weak mutation results showing that W ¯ is an increasing function of population size and a decreasing function of n, these parameters may have opposite effects in sexual populations at high mutation rate.